Determinants of Youths’ Intention to Shop Online: Study of Uganda and Rwanda - Kagoya, Sumaya M.; Mkwizu, Kezia H. (African Journals Online (AJOL), 2023)
Existing literature on online shopping has focused on reasons for people to shop online while there is limited research on youths’ intention to shop online. Hence, this paper was motivated to examine the determinants of youth’s intention to shop online by comparing two countries namely Uganda and Rwanda. This paper’s specific objectives are; to analyse the relationship between hedonic and satisfaction among youths to shop online and to analyse the relationship between subjective norms and satisfaction among youths to shop online. This is a quantitative study that used structured questionnaires which were circulated by email survey to 122 youths of higher education institutions in Uganda (Makerere University Business School) and Rwanda (University of Rwanda). The data was analysed using descriptive statistics and Partial Least Square Structural Equation Modelling (PLS-SEM). The findings indicated a significant relationship between hedonic and satisfaction among youths’ intention to shop online (p=0.000 for Uganda; p=0.05 for Rwanda); and a significant relationship between subjective norms and satisfaction among youths’ intention to shop online (p=0.02 for Uganda; p=0.000 for Rwanda). The practical implication is for stakeholders of online shopping and policy makers to consider hedonic and subjective norms as key factors that determine youths’ intention to shop online